2023
DOI: 10.1007/s00406-023-01570-5
|View full text |Cite
|
Sign up to set email alerts
|

Arketamine for cognitive impairment in psychiatric disorders

Abstract: Cognitive impairment has been observed in patients with various psychiatric disorders, including schizophrenia, major depressive disorder (MDD), and bipolar disorder (BD). Although modern therapeutic drugs can improve certain symptoms (i.e., psychosis, depression) in these patients, these drugs have not been found to improve cognitive impairment. The N-methyl-D-aspartate receptor antagonist (R,S)-ketamine has attracted attention as a rapidly acting antidepressant. In addition to its robust antidepressant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 155 publications
1
9
0
Order By: Relevance
“…This beneficial effect of (R)-ketamine could be blocked by ANA-12 pretreatment, a TrkB inhibitor, which suggests that this effect is possibly exerted via the activation of the BDNF-TrkB signaling, as well. Based on this, (R)-ketamine has been suggested as a potential therapeutic drug for disorders with cognitive impairment [ 7 , 17 ]. Theta rhythm has been shown to have a crucial role in cognitive processes (learning and memory) and in the control of complex behaviors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect of (R)-ketamine could be blocked by ANA-12 pretreatment, a TrkB inhibitor, which suggests that this effect is possibly exerted via the activation of the BDNF-TrkB signaling, as well. Based on this, (R)-ketamine has been suggested as a potential therapeutic drug for disorders with cognitive impairment [ 7 , 17 ]. Theta rhythm has been shown to have a crucial role in cognitive processes (learning and memory) and in the control of complex behaviors [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research indicates that ( R,S )-ketamine has enhance cognitive functions in patients with MDD. 20 , 21 Zhang et al 5 observed spatial working memory deficits in CCI mice lasting at least 21 days. In contrast, our study found that repeated doses of ( S )-ketamine (10 mg/kg/day for 5 days), unlike a single dose, effectively reversed spatial working memory impairment in CCI mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the normalization of gut microbial composition is believed to play a role in the therapeutic effects of several drugs. 20 , 47–49 For example, alterations in gut microbiota may contribute to the antidepressant-like effect of ( S )-norketamine, a major metabolite of ( S )-ketamine, in an inflammatory model of depression. 50 In our current study, ( S )-ketamine restored the composition of the gut microbiota in CCI mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, synthesizing the above studies we can easily find that ( R )-ketamine has a weak inhibitory effect on cognition, may improve cognitive dysfunction caused by other causes (such as psychiatric disorders) to a certain extent ( Hashimoto, 2023 ), and may play a positive role in preventing or delaying the disease progression of AD, and it is expected to be a potential medication for preventing and treating cognitive deficits in patients in the future.…”
Section: Research On Non-depressive Conditionsmentioning
confidence: 99%